Non-extraction Orthodontic Treatment with Molar Distalization - Malik, Vikas; Yadav, Puneet; Grover, Seema; Chaudhary, Girish (Journal of Orofacial Research, 2012)
A case report of 16 years female who reported to department with chief complaint of irregularly placed front teeth and an unpleasant smile. Patient was diagnosed with class II div 2malocclusion with arch length discrepancy of 8.5 mm in maxilla with buccally placed maxillary canines. Molar distalization technique was planned using pendulum appliance. Molars weredistalized by 5 mm in the right, 6 mm in left maxillary arch. Crowding was relieved effectively utilizing space created by molar distalization. Class I molar and canine relation wasachieved and maxillary arch was aligned in 7 months.